EVALUATION OF LEED CERTIFIED GREEN BUILDINGS - Bayhan, Hasan Gokberk; Gurgun, Asli Pelin (ISEC PRESS, 2016)
Leadership in Environmental and Energy Design, LEED, is one of the most recognized green building certification systems in the world. Turkey is also one of the countries, where it is widely used. It offers different rating groups to address varying requirements of building and project types. LEED-v3 NC, the rating group for new construction, includes seven categories of credits: sustainable sites, water efficiency, energy and atmosphere, materials and resources, indoor air quality, innovation, and regional priority. The maximum achievable point is 110. Local conditions significantly affect the achievement of some of the credits, as LEED is originated in the USA. This study focuses on the assessment of 122 LEED-v3 NC certified buildings in Turkey, considering the points achieved in each category. The aim is to understand which categories are successfully fulfilled and more challenging for implementation. Analysis results show that buildings receive higher points from water efficiency, sustainable sites, innovation and regional priorities, when compared to indoor environmental quality, energy and atmosphere and material and resources categories in Turkey. The lowest category is identified as material and resources. This situation should lead the new projects taking precautions to this individual area especially at the beginning of planning step in construction process. Recognizing the successful implementations for earning points and the challenging issues in Turkish construction industry regarding green buildings can be of benefit for professionals in this area.
Keywords: Green building sector; v3-LEED NC; Success ratio; Material and resources; Engineering